Avifaunal Diversity and Community Structure in Universitas Brawijaya Forest, East Java, Indonesia - Agus Nurrofik; Muhammad Fathoni; Agung Sih Kurnianto; Luhur Septiadi; Nia Kurniawan (Journal of Tropical Biodiversity and Biotechnology, 2021)
Avifauna inhabiting the mountainous forest ecosystem is severely threatened by anthropogenic disturbances, especially in the Java island of Indonesia. Yet, efforts to monitor the avifauna diversity are lacking, including in one of the mountainous forest areas, Universitas Brawijaya Forest (UBF). In this study, information about diversity, community structure, feeding specialization, and conservation status of avifauna is presented. Observations were conducted from December 2019 to February 2020 on two designated tracks with different degree of disturbances. Data were analyzed based on their conservation status, local distribution, feeding specialization (Jaccard similarity index), species richness, total abundance, species diversity (Shannon-Wiener diversity index), and importance value index (IVI). A total of 51 species from 27 families were identified. Two species at risk (one Near Threatened and one Endangered) and 9 protected avifauna were noted. This study can be used as the baseline data for future conservation management in the UBF.